2006
DOI: 10.1080/03637750600873736
|View full text |Cite
|
Sign up to set email alerts
|

Deception Detection Accuracy is a Predictable Linear Function of Message Veracity Base-Rate: A Formal Test of Park and Levine's Probability Model

Abstract: This study provided the first empirical test of point predictions made by the Park-Levine probability model of deception detection accuracy. Participants viewed a series of interviews containing truthful answers, unsanctioned, high-stakes lies, or some combination of both. One randomly selected set of participants (n0/50) made judgments where the probability that each message was honest was P(H)0/.50. Accuracy judgments in this condition were used to generate point predictions generated from the model and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 24 publications
3
58
1
Order By: Relevance
“…Since the vast majority of deception experiments use base rates of 50% lies and 50% truths in the material that participants judge, this truth bias leads participants to underestimate the lies and reduces accuracy (Levine, Kim, Park, & Hughes, 2006;Levine, Park, & McCornack, 1999;Park & Levine, 2001). However, a truth bias may not significantly reduce deception accuracy in many naturally occurring situations because rates of deception are usually much lower than 50% of all interactions (DePaulo, Kashy, Kirkendol, Wyer, & Epstein, 1996;George & Robb, 2008;Hancock, Thom-Santelli, & Ritchie, 2004a;Serota, Levine, & Boster, 2010).…”
Section: Detection Of Deception and Truth Biasmentioning
confidence: 96%
“…Since the vast majority of deception experiments use base rates of 50% lies and 50% truths in the material that participants judge, this truth bias leads participants to underestimate the lies and reduces accuracy (Levine, Kim, Park, & Hughes, 2006;Levine, Park, & McCornack, 1999;Park & Levine, 2001). However, a truth bias may not significantly reduce deception accuracy in many naturally occurring situations because rates of deception are usually much lower than 50% of all interactions (DePaulo, Kashy, Kirkendol, Wyer, & Epstein, 1996;George & Robb, 2008;Hancock, Thom-Santelli, & Ritchie, 2004a;Serota, Levine, & Boster, 2010).…”
Section: Detection Of Deception and Truth Biasmentioning
confidence: 96%
“…Some cheated while others did not. Details regarding the process of creating the interview segments are reported in Levine, Kim, Park, and Hughes (2006). Based on the results of pilot testing, the stimulus tapes were modified for use in the current study by editing out the last interview question from each interview segment because that question implied suspicion, thereby negating the suspicion induction.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Despite earlier research suggesting few differences between sanctioned and unsanctioned deceivers (Feeley, 1996), other researchers have argued vociferously that the experimental setting must include unsanctioned lies in order to activate the guilt response of the participant (e.g., Levine et al, 2006). Although our research found little difference in the guilt experienced between sanctioned and unsanctioned liars and thus did not account for any differences between these two conditions, sanctioning of the lie did have an effect on the likelihood of confessions: Unsanctioned deceivers were far more likely to confess than were sanctioned deceivers.…”
Section: Sanctioningmentioning
confidence: 97%